Developing Philology Teachers’ Inclusive Competence in Postgraduate Education - Kazachiner, Olena (Educational Challenges, 2020)
This research focuses on the phenomenon of philology teachers’ inclusive competence development as a part of their professional competence. The purpose of the research is to substantiate scientifically the concept of inclusive competence development, to develop and experimentally test the system of philological disciplines teachers’ inclusive competence development in the system of postgraduate education. The following methodology tools were used as analysis, classification, and pedagogical experiments. As a result of this study, the pedagogical conditions for philological disciplines teachers’ inclusive competence development were singled out and theoretically substantiated. The first, stimulation of motivation of philological disciplines teachers to professional activity in the conditions of the inclusive educational environment. The second, updating the content of educational programs of advanced training courses for teachers of philological disciplines in view of the provisions of inclusive education. The third, combination of traditional and innovative forms and methods of teaching teachers of philological disciplines in postgraduate pedagogical education institutions for the implementation of inclusive education in general secondary education institutions. The last, involvement of language and literature teachers in team interaction with specialists of different profiles for the implementation of the tasks of inclusive education through these subjects in general secondary education institutions. It was experimentally proved that the introduction of the model of developing philological disciplines teachers’ inclusive competence in postgraduate education helps to increase their motivation to teaching languages and literature in the context of inclusion, interest in teaching children with special educational needs together with peers in general secondary education, acquisition and application of inclusive knowledge, d developing inclusive skills, as well as significantly affect the level of languages and literature teachers’ professional competence in general. It was concluded that the prepared scientific and methodological support positively influences the stimulation of the process of philological disciplines teachers’ inclusive competence development.